Writing Reflective Journals Influences Students Vocabulary Mastery - Umi Farisiyah (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
The concern of this study is to investigate the effectiveness of writing reflective journals right after having an English class on students vocabulary mastery. A reflective journal is a tool that allows students to reflect on and write about progress in their learning. They can identify and reflect on their successes and challenges. Teachers can gain information on what the students thinks and feel not in a threatening way. This study is conducted through a quasi experimental study which aims to determine whether writing reflective journals can improve students vocabulary mastery. A total of 50 students (two classes having the same ability) from the second grade of one Senior High School in Brebes, Central Java, participated in this study. The participants are divided into two groups ( an experimental group and a control group) based on a purposive sampling. The two groups will be given two tests ( a Pretest and a post Test). The result of the study and hypothesis testing concluded that there are significant differences in vocabulary mastery of students asked to compose a reflective journal every after finishing English class with students that are not asked to do so. In other words, Increasing the ability to master vocabularies of the experimental group is better than the control one.